2015
DOI: 10.3109/0886022x.2015.1057799
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of thrombocytopenia associated with continuous renal replacement therapy in critically ill patients

Abstract: Introduction: Thrombocytopenia in the intensive care unit (ICU) is a commonly experienced complication; the pathology is not always easily understood. Continuous renal replacement therapy (CRRT) provides a method to dialyze unstable critically ill patients. We hypothesized that CRRT may precipitate a form of thrombocytopenia. In trials thrombocytopenia occurred at rates as high as 70%. The etiology remains unknown and results in additional diagnostic workup, as well as possible drug therapy. The extent, durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 13 publications
4
52
0
Order By: Relevance
“…This may explain the high mortality in critically ill patients receiving CRRT (93·8%, 15/16). As an important supportive treatment for critically ill patients with sepsis or AKI, CRRT is used to efficiently remove proinflammatory mediators accumulated in the blood and maintain fluid balance in hemodynamically unstable patients, 35 which has been recommended for renal failure and renal replacement therapy in the Chinese Clinical Guidance for COVID-19. 36 However, accumulating clinical data showed that there were nearly no survivors among critical COVID-19 patients who received CRRT treatment, indicating that patients did not benefit from CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the high mortality in critically ill patients receiving CRRT (93·8%, 15/16). As an important supportive treatment for critically ill patients with sepsis or AKI, CRRT is used to efficiently remove proinflammatory mediators accumulated in the blood and maintain fluid balance in hemodynamically unstable patients, 35 which has been recommended for renal failure and renal replacement therapy in the Chinese Clinical Guidance for COVID-19. 36 However, accumulating clinical data showed that there were nearly no survivors among critical COVID-19 patients who received CRRT treatment, indicating that patients did not benefit from CRRT.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia is reported to occur in three‐fourths of patients receiving continuous renal‐replacement therapy (Ferreira & Johnson, ). Immune destruction, co‐morbid conditions and secondary to drugs (including heparin) used in these patients are mechanisms described but the dialysis‐specific issues are related to the adherence of platelets to the dialysis‐filtration membrane (Ferreira & Johnson, ). Dialyzer membrane‐induced thrombocytopenia was first noted three decades ago by Vicks et al () prior to routine blood counts when patients developed haemorrhage related to thrombocytopenia.…”
Section: Practice Pointers To Identify a Cause Of Thrombocytopenia Inmentioning
confidence: 99%
“…However, less is known about the ideal circumstances in which RRT may be successfully discontinued. RRT is a complex and expensive therapy, with complications including catheter-associated infections, hemorrhage, hemodynamic instability, and delayed renal recovery [7][8][9][10][11][12][13][14][15]. It is thus imperative to recognize when a patient may be safely liberated from this treatment.…”
Section: Introductionmentioning
confidence: 99%